Investigation of In-vitro antioxidant potential, brine shrimp lethality and Thrombolytic activity in Ficus mollis vahl Leaves along with phytochemical screening - Sarkar, Mahin (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.